2020
DOI: 10.1128/msystems.00497-20
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of REBASE Identifies Numerous Type I Restriction-Modification Systems with Duplicated, Distinct hsdS Specificity Genes That Can Switch System Specificity by Recombination

Abstract: N6-Adenine DNA methyltransferases associated with some Type I and Type III restriction-modification (R-M) systems are able to undergo phase variation, randomly switching expression ON or OFF by varying the length of locus-encoded simple sequence repeats (SSRs). This variation of methyltransferase expression results in genome-wide methylation differences and global changes in gene expression. These epigenetic regulatory systems are called phasevarions, phase-variable regulons, and are widespread in bacteria. A … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 44 publications
3
31
1
Order By: Relevance
“…A thorough understanding of phase variation of gene expression, and in particular of phasevarions, is required in order to determine the stably expressed antigenic repertoire of a bacterial species. The prevalence of phase-variable methyltransferases across the bacterial domain demonstrates that phasevarions are a widespread contingency strategy (22,45,46) and that characterization of these systems is imperative in order to rationally design effective vaccines that only target stably expressed antigens in the organisms where they are present.…”
Section: Discussionmentioning
confidence: 99%
“…A thorough understanding of phase variation of gene expression, and in particular of phasevarions, is required in order to determine the stably expressed antigenic repertoire of a bacterial species. The prevalence of phase-variable methyltransferases across the bacterial domain demonstrates that phasevarions are a widespread contingency strategy (22,45,46) and that characterization of these systems is imperative in order to rationally design effective vaccines that only target stably expressed antigens in the organisms where they are present.…”
Section: Discussionmentioning
confidence: 99%
“…Phasevarions can be identified by known markers of phase variation, such as simple sequence repeats (SSRs) within promoters or gene bodies and hsdS genes flanked by inverted repeats. Systematic surveys have identified 13.8% Type I and 17.4% Type III RMSs as being potentially phase variable (22)(23)(24). Several clinically relevant pathogens such as Helicobacter pylori (25,26), Neisseria meningitidis (27), Neisseria gonorrhoeae (28,29), Haemophilus influenzae (30,31), Moraxella catarrhalis (32,33), and Kingella kingae (34) harbor such phase variable RMSs.…”
Section: Introductionmentioning
confidence: 99%
“…In order to thoroughly characterise each phasevarion, further analysis will be needed. It will also be important to characterisation the phasevarions controlled by other modS alleles; in previous work we showed that a third (22,43,44), and that characterisation of these systems is imperative in order to rationally design effective vaccines that only target stably expressed antigens in the organisms where they are present.…”
Section: Discussionmentioning
confidence: 99%
“…A thorough understanding of phase variation of gene expression, and in particular phasevarions, is required in order to determine the stably expressed antigenic repertoire of a bacterial species. The prevalence of phase variable methyltransferases across the bacterial domain demonstrates that phasevarions are a widespread contingency strategy (22,43,44), and that characterisation of these systems is imperative in order to rationally design effective vaccines that only target stably expressed antigens in the organisms where they are present.…”
Section: Ms Is a Technique Which Quantitates Protein Expression Based On Abundance (41)mentioning
confidence: 99%